Princess ever after [large type] - Hauck, Rachel, 1960- (Hauck, Rachel, 1960- Royal wedding novel, 2014)
Regina Beswick never dreamed of faraway places. She's happy with her life as a classic car mechanic and owner of a restoration shop. But an unexpected visitor and the discovery of a fairytale drawn by her great-grandma causes Regina to wonder if she might be destined for something more... Tanner Burkhardt, Minister of Culture for the Grand Duchy of Hessenberg, must convince the strong-willed Southern belle that she is his country's long-lost princess. Failure could destroy his reputation and change his nation forever. As Regina and Tanner face the challenges before them, neither are prepared for love to invade their hearts and change every thing they believe about themselves. However, when a royal opponent nearly destroys Regina's future, she must lean into God and trust He has sovereignly brought her to her true and final destiny.